2010
DOI: 10.1111/j.1365-246x.2010.04552.x
|View full text |Cite
|
Sign up to set email alerts
|

Seismic evidence for fluids in fault zones on top of the subducting Cocos Plate beneath Costa Rica

Abstract: S U M M A R YIn the 2005 TICOCAVA explosion seismology study in Costa Rica, we observed crustal turning waves with a dominant frequency of ∼10 Hz on a linear array of short-period seismometers from the Pacific Ocean to the Caribbean Sea. On one of the shot records, from Shot 21 in the backarc of the Cordillera Central, we also observed two seismic phases with an unusually high dominant frequency (∼20 Hz). These two phases were recorded in the forearc region of central Costa Rica and arrived ∼7 s apart and 30-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 80 publications
2
12
0
Order By: Relevance
“…Some earlier geodynamic modeling studies [ van Keken et al , 2002; Conder , 2005; Wada et al , 2008] concluded that a thin weak layer on the plate interface is necessary to obtain a realistic temperature structure in the mantle wedge, and to match heat flow profiles across the convergent margin at the Earth's surface. There is some geophysical evidence for such a thin, weak plate boundary beneath the forearc [ Audet et al , 2009; Van Avendonk et al , 2010], but such observations do not rule out the possibility that some subduction zones have a strong plate interface. A large number of subduction zones have a seismogenic zone dip angle θ > 20° (Figure 2) suggests that the friction angle ϕ is often significantly larger than 1°.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some earlier geodynamic modeling studies [ van Keken et al , 2002; Conder , 2005; Wada et al , 2008] concluded that a thin weak layer on the plate interface is necessary to obtain a realistic temperature structure in the mantle wedge, and to match heat flow profiles across the convergent margin at the Earth's surface. There is some geophysical evidence for such a thin, weak plate boundary beneath the forearc [ Audet et al , 2009; Van Avendonk et al , 2010], but such observations do not rule out the possibility that some subduction zones have a strong plate interface. A large number of subduction zones have a seismogenic zone dip angle θ > 20° (Figure 2) suggests that the friction angle ϕ is often significantly larger than 1°.…”
Section: Discussionsupporting
confidence: 89%
“…The in situ friction coefficient of the sediment and serpentinized peridotite is not well constrained from lab experiments. The possible presence of pore fluid would decrease the effective friction coefficient further at the subduction interface at a wide range of depths [e.g., Moore et al , 1995; Wada et al , 2008; Audet et al , 2009; Van Avendonk et al , 2010]. In our geodynamic models we will assume that the friction angle ϕ of the sediments and that of serpentine vary similarly, and we will vary ϕ as a controlling parameter.…”
Section: Geophysical Observationsmentioning
confidence: 99%
“…This suggests that the added pore pressure and the presence of hydrous minerals might be one of key factors to explain the low S wave velocity (or high Poisson's ratio) in the horizontal part of the upper oceanic crust. Also, the friction across the slab interface may be further reduced by high fluid pressures as a result of metamorphic dehydration of the slab [ Van Avendonk et al , 2010]. The influence of the pore pressure on seismic velocities is however expected to be diminish with depth and is unlikely to be significant at lower oceanic crustal depths where the porosity is extremely low [ Christensen , 1984].…”
Section: Discussionmentioning
confidence: 99%
“…[] that relamination of subducted sediments and eroded material from the upper plate is a mechanism for thickening arc crust and recycling continental material. Assuming a constant subduction rate of ~87 mm/yr [ DeMets , ] since ~65 Ma [ Meschede and Frisch , ] with a thickness of sediments subducted ~0.5 km [ Ivandic et al ., ; van Avendonk et al ., ] and density change of ~300 kg/m 3 [ Hacker et al ., ], the total cross‐sectional area of subducted sediments over the life of the MAT can be estimated as ~2500 km 2 . Given the approximate cross‐sectional area of our profile (~4800 km 2 ) and the estimated area of preexisting CLIP across our profile (~2000 to ~3000 km 2 ) from assuming a 12–20 km thickness found in studies of the adjacent Colombian Basin [ Case et al ., ], if all subducted sediment were relaminated beneath the arc, the expected volume would completely fill the available crustal space, leaving no room for new material from arc‐related intrusions.…”
Section: Discussionmentioning
confidence: 99%